2012
DOI: 10.1007/s13197-012-0804-y
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of aqueous extract of some food grain powder in meat model system

Abstract: In-vitro antioxidant activity of some food grains [sprouted mung bean (Vigna radiata), mung bean, sprouted chana (Cicer arietinum), chana, corn (Zea mays), methi (Trigonella foenum-graecum) and rajma (Phaseolus vulgaris)] powder extracts (FGE) was estimated by DPPH free radical scavenging activity (SA) method. Total phenolics and reducing power were also estimated in these extracts. The antioxidant potential of these extracts was also estimated in a meat model system. Total phenolics in FGE ranged from 66.9±3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Popping resulted in a significant ( p < .05) decrease in DPPH activity in popped makhana, which might be due to the decomposition of phytochemicals (Mir et al., 2016) and separation of bran during popping. It was also reported in earlier studies that higher concentration of phenolics and flavonoids was positively correlated with DPPH radical scavenging activity (Yogesh, Jha, & Ahmad, 2014). It may, therefore, be inferred that the phenolics, flavonoids, and phytic acids were mainly concentrated in the bran as discussed in earlier sections and hence the antioxidant activity of bran was more.…”
Section: Resultssupporting
confidence: 67%
“…Popping resulted in a significant ( p < .05) decrease in DPPH activity in popped makhana, which might be due to the decomposition of phytochemicals (Mir et al., 2016) and separation of bran during popping. It was also reported in earlier studies that higher concentration of phenolics and flavonoids was positively correlated with DPPH radical scavenging activity (Yogesh, Jha, & Ahmad, 2014). It may, therefore, be inferred that the phenolics, flavonoids, and phytic acids were mainly concentrated in the bran as discussed in earlier sections and hence the antioxidant activity of bran was more.…”
Section: Resultssupporting
confidence: 67%
“…Phenolics compounds have been reported to be crucial for major portion of the antioxidant capacity in many plants (Yogesh et al, 2014). In the current study, YTP demonstrated the highest TPC activity of 26.2 ± 0.04 gallic acid equivalent/g extract while YB had the least activity of 2.06 ± 0.00 gallic acid equivalent/g extract (P <0.05) (Table 2).…”
Section: Discussionsupporting
confidence: 52%
“…Proximate composition shows carbohydrate content in the range of (68.73±0.05e -72.17±0.01 a). Yogesh et al (2014). They noticed that total phenolic contents were in range of 66.9±3.4 to 248.6±0.67mg/g.Total flavonoid contents were in the range of 2.59 GAE/g -36.49 GAE/g (Table 3).…”
Section: Resultsmentioning
confidence: 97%